The EEE Multigap Resistive Plate Chambers as tracking devices to monitor the stability of a civil building. (23rd April 2021) - Pinto, C.; Abbrescia, M.; Avanzini, C.; Baldini, L.; Baldini Ferroli, R.; Batignani, L.G.; Battaglieri, M.; Boi, S.; Bossini, E.; Carnesecchi, F.; Cicalò, C.; Cifarelli, L.; et al.
Abstract: Due to their efficiency, tracking capabilities and long-term operational conditions, Multigap Resistive Plate Chambers (MRPC) may be used in a stable location in coincidence with additional detectors fixed to other parts of a civil building, to detect relative displacements of different parts of the building due to long term deformations of the structure. In this contribution we report the results of two different measurements carried out in the Department of Physics and Astronomy of the University of Catania (with three floors above the ground and an underground basement), using one of the MRPC telescopes of the Extreme Energy Events project, in coincidence with two scintillator-based muon telescopes located in various positions inside the building. Experimental results obtained by these measurements campaigns over a period of about three months are reported, together with a discussion about the performance of the technique. The sensitivity of the method is also discussed by means of Monte Carlo simulations.